2011
DOI: 10.1177/0020872811400717
|View full text |Cite
|
Sign up to set email alerts
|

Coproduction, participation and satisfaction with rehabilitation services following the 2001 earthquake in Gujarat, India

Abstract: The most successful post-earthquake rehabilitation program is the one that involves the victims in their own relief, reconstruction, and rehabilitation efforts. The role of the government and NGOs is to facilitate people’s participation. This article explores the concept of coproduction in action in the 2001 post-earthquake rehabilitation in Gujarat, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
2
9
0
2
Order By: Relevance
“…These results corroborate the innovation theories, which state that organizations tend to focus on innovations related mainly to efficiency, developing new services and enhancing user experience and satisfaction (Bitner & Brown, 2008). This study has also demonstrated empirically that coproduction in public services brings results that add value to the citizen, by increasing the quality of the service provided and for the provider organization, corroborating the literature (Brudney & England, 1983;Kelley et al, 1990;Pestoff, 2012;Thomas et al, 2011). Furthermore, the results confirming the findings of Needham (2008) have proven that the citizen's experience with the judicial conciliation service depends almost entirely on coproduction, that is, the more interaction with the other litigant party, the more able the service is to add value for the user.…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
See 1 more Smart Citation
“…These results corroborate the innovation theories, which state that organizations tend to focus on innovations related mainly to efficiency, developing new services and enhancing user experience and satisfaction (Bitner & Brown, 2008). This study has also demonstrated empirically that coproduction in public services brings results that add value to the citizen, by increasing the quality of the service provided and for the provider organization, corroborating the literature (Brudney & England, 1983;Kelley et al, 1990;Pestoff, 2012;Thomas et al, 2011). Furthermore, the results confirming the findings of Needham (2008) have proven that the citizen's experience with the judicial conciliation service depends almost entirely on coproduction, that is, the more interaction with the other litigant party, the more able the service is to add value for the user.…”
Section: Conclusion and Recommendationssupporting
confidence: 88%
“…Some studies have already found that coproduction is associated with the users' better perception of the quality and added value by the service (Anderson & Sullivan, 1993;Kelley, Donnelly, & Skinner, 1990;Pestoff, 2012;Thomas, Ott, & Liese, 2011). Troye and Supphellen (2012) agree with this relationship when stating that the user participation in the service delivery process can be linked to growing satisfaction both with the service provided and its results.…”
Section: Coproduction In Public Servicesmentioning
confidence: 90%
“…They also point to the importance of building community capacities before and after the earthquakes (in terms of relationships with the wider community, employment and access to education, etc.). As Thomas, Ott, and Liese (2011) argue, programmes that involve the people and communities impacted by the disaster in the response and subsequent reconstruction and redevelopment should be central to a social work response. Pyles (2007) notes, however, that social work does not necessarily have a strong history of community organising in pre-and post-disaster contexts where people can come together to establish local responses to such events.…”
Section: Discussion -Implications For a Social Work Responsementioning
confidence: 99%
“…Algumas pesquisas já constataram que a coprodução está associada com a melhoria na percepção dos usuários da qualidade e do valor gerado pelo serviço (Kelley, et al, 1990;Anderson & Sullivan, 1993;Warren, 1987;Thomas, Ott & Liese, 2011 …”
Section: Efeitos Da Coprodução E a Satisfação Dos Usuários Do Serviçounclassified
“…Esta pesquisa também demonstrou, empiricamente, que a coprodução adiciona valor para os clientes (Zeithaml et al, 2008), da mesma forma que a coprodução em serviços públicos apresenta resultados positivos para o cidadão, por meio do aumento da qualidade do serviço prestado (Kelley et al, 1990;Brudney & England, 1983;Thomas et al, 2011;Pestoff, 2012).…”
Section: Conclusões E Recomendaçõesunclassified